The IgH Eµ-MAR regions promote UNG-dependent error-prone repair to optimize somatic hypermutation - Martin, Ophélie A.; Thomas, Morgane; Marquet, Marie; Bruzeau, Charlotte; Garot, Armand; Brousse, Mylène; Bender, Sébastien; Carrion, Claire; Choi, Jee Eun; Vuong, Bao Q.; Gearhart, Patricia J.; Maul, Robert W.; et al. (Frontiers in Immunology, 2023)
Two scaffold/matrix attachment regions (5’- and 3’-MARsEµ) flank the intronic core enhancer (cEµ) within the immunoglobulin heavy chain locus (IgH). Besides their conservation in mice and humans, the physiological role of MARsEµ is still unclear and their involvement in somatic hypermutation (SHM) has never been deeply evaluated. By analysing a mouse model devoid of MARsEµ, we observed an inverted substitution pattern: SHM being decreased upstream from cEµ and increased downstream of it. Strikingly, the SHM defect induced by MARsEµ-deletion was accompanied by an increase of sense transcription of the IgH V region, excluding a direct transcription-coupled effect. Interestingly, by breeding to DNA repair-deficient backgrounds, we showed that the SHM defect, observed upstream from cEµ in this model, was not due to a decrease in AID deamination but rather the consequence of a defect in base excision repair-associated unfaithful repair process. Our study pointed out an unexpected “fence” function of MARsEµ regions in limiting the error-prone repair machinery to the variable region of Ig gene loci.